Pengaruh Variasi Waktu Perendaman Terhadap Sifat Dan Karakteristik Campuran Aspal Panas Dengan Penambahan Styrofoam - Linus, Jusat Simon; Mallawangeng, Tamrin; Lebang, Fauzy (Program Studi Teknik Sipil Universitas Bosowa, 2023)
Hot Rolled Sheet (HRS) According to the Ministry of Public Works (Bina Marga revision 2010), a thin layer of asphalt concrete (lataston) is a cover layer consisting of a mixture of gap graded aggregate, filler and hard asphalt with a certain ratio; which is mixed and hot compacted (within a certain temperature, a minimum of 124ºC). The purpose of this study was to determine the effect of variations in immersion time on the properties and characteristics of asphalt with Styrofoam added. This study used Styrofoam food waste with the addition of 5%, 10%, and 20%. Samples of specimens were made as many as 48 samples, 15 normal samples and 27 variations samples, 6 samples of remaining KAO. Treatment of the specimens was carried out with repeated immersion variations of 3, 7, and 14 days. The manufacture of test objects is hot mixed and refers to the 2018 Bina Marga Specifications, the test is carried out with the Marshall test equipment. The results of this test, indicate that the effect of Styrofoam waste as an additive in the HRS type asphalt mixture with repeated immersion can decrease the value of density, stability, MQ, and VFB. While the value of flow, VMA, and VIM increased